Construction of PLS-SEM Model of Organisational Factors Affecting the Efficiency of Emarati Electronic Government Procurement Platform (EEGPP) Implementation in UAE - Maimunah Ali; Faisal Obaid Obaid (International Journal of Sustainable Construction Engineering and Technology, 2022)
The United Arab Emirates (UAE) government paid a lot of attention to enhancing its e-government services, including the e-government procurement platform (E-GPP). Due to lack of study regarding the efficiency of E-GPP implementation, this research aimed to develop a PLS-SEM model of organizational factors affecting the efficiency of Emarati Electronic Government Procurement Platform (EEGPP) of UAE government. This study adopted the quantitative research approach where the survey data from 206 participants were used to develop and analyse the model using SmartPLS software. The model was evaluated and found that it achieved GoF value of 0.690 which indicate having high validating power. Futher analysis on the model, found that planning, policy formulation, change management, and human resource management constructs have significant effect on the efficiency of the EEGPP. Mediating effect of innovation construct also revealed that innovation has a significant mediating effect on the relationship between the four independent variables (planning, policy formulation, change management, and human resource management) and the efficiency of the EGPP of the UAE. This model and the outcomes of this research can contribute significantly to policy and decision-makers during focusing on the planning, policy formulation, change management, and human resource management in the implementation of the EGPP.